Pengaruh Model Peer-Led Team Learning Terhadap Hasil Belajar Siswa Kelas XI SMA N 1 Tomohon Pada Materi Hidrokarbon - Aror, Carolina Gabriella Gracilia; Gugule, Sanusi (Chemistry Department, Universitas Negeri Manado, 2024)
This research was conducted to see whether there is an effect of using the Peer-Led Team Learning model on the learning outcomes of class XI SMA N 1 Tomohon students on the Hydrocarbons topic. The effect is seen from the different in learning outcomes between the class with the Peer-Led Team Learning model and the class with conventional learning. The type of this research is quantitative with experimental design. Data collection techniques are carried out by giving pre-test and post-test in the experimental class and control class. The hypothesis was tested with the independent-t test. The test result showed the tcount is 6,029, 6,029 > 2,007584. The conclusion is to accept Ha namely that there is significant different between the learning outcomes of class with the Peer-Led Team Learning model and class with conventional learning. After the hypothesis test, an N-Gain test was carried out to determine the effectiveness of using the learning model. The test results showed an N-Gain value in the experimental class of 0.70 with a percentage 70.02148%, and in the control class of 0.50 with a percentage 50.38885%. Based on these results, it is known that the use of the Peer-Led Team Learning model is more effective than conventional learning.